Oligodendrocyte precursor cell specification is regulated by bidirectional neural progenitor-endothelial cell crosstalk - Paredes Ugarte, Isidora B.; Cruz Vieira, José Ricardo da; Shah, Bhavin; Ramunno, Carla F.; Dyckow, Julia; Adler, Heike; Richter, Melanie; Schermann, Géza; Giannakouri, Evangelia; Schirmer, Lucas; Augustin, Hellmut; Ruiz de Almodóvar, Carmen (Nature neuroscience, 2021)
Neural-derived signals are crucial regulators of CNS vascularization. However, whether the vasculature responds to these signals by means of elongating and branching or in addition by building a feedback response to modulate neurodevelopmental processes remains unknown. In this study, we identified bidirectional crosstalk between the neural and the vascular compartment of the developing CNS required for oligodendrocyte precursor cell specification. Mechanistically, we show that neural progenitor cells (NPCs) express angiopoietin-1 (Ang1) and that this expression is regulated by Sonic hedgehog. We demonstrate that NPC-derived Ang1 signals to its receptor, Tie2, on endothelial cells to induce the production of transforming growth factor beta 1 (TGFβ1). Endothelial-derived TGFβ1, in turn, acts as an angiocrine molecule and signals back to NPCs to induce their commitment toward oligodendrocyte precursor cells. This work demonstrates a true bidirectional collaboration between NPCs and the vasculature as a critical regulator of oligodendrogenesis.
Gesehen am 02.08.2021